Comparison of the Effect of Eight Weeks Resistance, Balance, and Combined Training Program on Balance, Gait, and Quality of Life in Patients with Multiple Sclerosis: A Pretest-Posttest Intervention - Maryam Mohamadzadeh; Nader Rahnama; Shahnaz Shahrbanian; Yousef Moghadas-Tabrizi (Vesnu Publications, 2017)
Introduction: Exercise therapy is a supplementary method for the rehabilitation of patients with multiple sclerosis (MS). The aim of this study was to compare the efficacy of an 8-week balance, resistance, and combined (balance-resistance) exercise program on balance, gait, and quality of life (QOL) in women with MS. Materials and Methods: In the present study, 30 women with MS (mean ± standard deviation of age: 34.6 ± 4.1) were randomly divided into balance, resistance, and combined exercise groups. The Berg Balance Scale, six-minute walk test (6MWT), Multiple Sclerosis Quality of Life-54 (MSQOL-54) questionnaire, and the Expanded Disability Status Scale (EDSS) were used, respectively, to evaluate balance, gait, and QOL. Patients underwent 3 separate intervention protocols for 8 weeks. The ANOVA, Tukey's post hoc test, and paired t-test were used for statistical analysis (P < 0.05). Results: Balance and resistance exercises improved balance and resistance and combined exercises improved gait, but they did not significantly affect the patients' QOL. Conclusion: It can be concluded that balance and resistance exercises have a positive effect on balance and combined and resistance exercise has positive effects on gait; thus, they can be recommended as a supplementary rehabilitation intervention for women with MS.